The Laghusiddhāntakaumudī of Varadarāja : a primer of Pāṇini's grammar. . Vol. 1 - Varadarāja (Motilal Banarasidass Publishers, 2010)
Abridgment of Siddhāntakaumudī by Bhaṭṭojī Dīkṣita, classical commentary on Aṣṭādhyāyī of Pāṇini, work on Sanskrit grammar.